A series of network structure reinforced phase reinforced aluminum matrix composite material and preparation method thereof

By using laser powder bed melting technology to prepare the series mesh-like reinforced phase in aluminum-based composite materials, the problems of limited reinforcement effect of existing aluminum-based composite materials and uneven distribution of ceramic reinforced phases are solved, and laser forming and mechanical properties are achieved Improvement.

CN116815020BActive Publication Date: 2025-02-18NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310726278.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-02-18
Estimated Expiration
2043-06-19

AI Technical Summary

Technical Problem

The reinforcement effect of existing aluminum-based composite materials is limited, and traditional processing technology leads to uneven distribution of ceramic reinforced phases and poor overall performance.

Method used

The series mesh reinforced phase reinforced aluminum matrix composite material is prepared by laser powder bed melting technology. By uniformly dispersing Al11X3 and Al3Ti series mesh reinforced phases in the aluminum alloy matrix, the in-situ reaction is formed during laser forming using TiH2 and XB6 powders. This structure.

Benefits of technology

The laser forming properties and mechanical properties have been significantly improved. The series network-like structure reinforced phase, as a heterogeneous nucleation point, promotes the refinement of the crystal structure of aluminum alloy, and achieves the synergistic effect of solid solution strengthening and fine crystal strengthening.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116815020B_ABST
    Figure CN116815020B_ABST
Patent Text Reader

Abstract

The invention discloses a series network structure reinforced phase reinforced aluminum-based composite material and a preparation method thereof, comprising an aluminum alloy matrix and Al uniformly dispersed in the aluminum alloy matrix. 11 X3 and Al3Ti are connected in series to form a network structure reinforcement phase; wherein the aluminum alloy matrix is ​​aluminum-copper-lithium-nickel-zirconium alloy; the X is selected from any one of Ce, La, Nd, etc.; the Al 11 X3 and Al3Ti series network structure reinforcement phase with Al 11 X3 is the main chain, Al3Ti is the node, and the series network structure reinforcement phase is evenly distributed in the aluminum alloy matrix. The present invention first discovered that during the laser forming process, TiH2 and XB6 powders will react in situ in the molten pool to form Al 11 The series network structure with X3 as the main chain and Al3Ti as the nodes can act as a heterogeneous nucleation point to promote the transformation of coarse columnar crystals into fine equiaxed crystals in aluminum alloys, and can play a role in solid solution strengthening and grain refinement, thus achieving a significant improvement in laser formability and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ceramic reinforced aluminum-based composite materials, and particularly relates to a series network structure reinforced phase reinforced aluminum-based composite material and a preparation method thereof. Background Art

[0002] Aluminum-based composites have excellent properties such as high specific strength, good thermal stability, and good wear resistance, and have broad application prospects in the fields of aerospace and automobiles. At present, most aluminum-based composites are based on single ceramic reinforcement, and the microstructure characteristics are not obvious. With the continuous improvement of modern industry's requirements for material performance, single-reinforced aluminum-based composites have encountered bottlenecks due to their single strengthening effect. Customizing special structures through complex or multi-phase reinforced aluminum-based composites provides a new idea for improving the performance of aluminum-based composites. It can combine the advantages of different reinforcement phases to achieve customized reinforcement structure preparation. Therefore, customized complex-phase reinforced aluminum-based composites are of great significance to the development and application of aluminum-based composites.

[0003] From the perspective of processing technology, traditional processing technologies such as casting, forging, and powder metallurgy are prone to uneven distribution of ceramic reinforcement phases, difficult to control size and shape, and poor interface bonding between ceramic reinforcement phases and matrix due to differences in composition, crystal structure, and physical and chemical properties between the ceramic phase and the metal matrix, resulting in poor overall performance of aluminum-based composites. Laser powder bed melting technology is a new type of laser additive manufacturing technology. It is a process that uses high-intensity laser as an energy source to melt powder layer by layer according to computer-aided design (CAD) data to form parts. It is widely used due to its high dimensional accuracy, high cooling rate, and the ability to customize certain complex structural components. Under the action of a high-energy laser beam, the powder particles are completely melted, so that adjacent scanning tracks or layers are well metallurgically bonded, improving the formability and performance of aluminum-based composite parts. Therefore, the use of laser powder bed melting technology to form aluminum-based composites has great development potential. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a series network structure reinforced phase reinforced aluminum-based composite material and a preparation method thereof in view of the shortcomings of the prior art, so as to overcome the problem of limited strengthening effect of the existing aluminum-based composite materials and achieve improvement in laser formability and mechanical properties.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A series network structure reinforced phase reinforced aluminum matrix composite material, comprising an aluminum alloy matrix and Al uniformly dispersed in the aluminum alloy matrix 11 X3 and Al3Ti tandem network structure reinforcement phase;

[0007] Wherein, the aluminum alloy matrix is ​​aluminum-copper-lithium-nickel-zirconium alloy; the X is selected from any one of Ce, La, Nd, etc.;

[0008] The Al 11 X3 and Al3Ti series network structure reinforcement phase with Al 11 X3 is the main chain, Al3Ti is the node, and the series network structure reinforcement phase is evenly distributed in the aluminum alloy matrix.

[0009] Furthermore, the present invention also provides a method for preparing the above-mentioned series network structure reinforced phase reinforced aluminum-based composite material, comprising the following steps:

[0010] (1) uniformly mixing TiH2 metal powder, XB6 ceramic powder and aluminum alloy matrix powder to obtain a composite powder;

[0011] (2) Establishing a 3D solid geometric model of the target part, slicing the model and planning the laser scanning path, discretizing the 3D solid into a series of 2D data, saving and importing it into the laser powder bed fusion forming equipment;

[0012] (3) The laser powder bed fusion forming equipment rapidly melts and solidifies the composite powder in step (1) layer by layer according to the file imported in step (2).

[0013] Preferably, in step (1), the particle size of the TiH2 metal powder is in the range of 2 to 5 μm, and the purity is greater than 99.5%.

[0014] Preferably, in step (1), the XB6 ceramic powder has a particle size ranging from 2 to 5 μm and a purity greater than 99.5%.

[0015] Furthermore, in step (1), the mass ratio of the TiH2 metal powder to the XB6 ceramic powder is 3:1 to 1:5, preferably 1:1; the total mass of the TiH2 metal powder and the XB6 ceramic powder accounts for 1 to 5 wt.% of the mass of the aluminum alloy matrix powder, preferably 2 wt.%.

[0016] Preferably, in step (1), the aluminum alloy matrix powder is an aluminum-copper-lithium-nickel-zirconium alloy, wherein the copper content is 3.0-4.2wt.%, the lithium content is 0.6-1.7wt.%, the nickel content is 0.15-0.90wt.%, the zirconium content is 0.1-0.8wt.%, and the remainder is Al; the aluminum alloy powder particle size distribution range is 21-52μm, and the purity is greater than 99.5%.

[0017] Specifically, in step (1), TiH2 metal powder, XB6 ceramic powder and aluminum alloy matrix powder are uniformly mixed by ball milling in a planetary ball mill under the protection of an inert gas, wherein the inert gas is preferably argon.

[0018] Preferably, the planetary ball mill is a QM series planetary ball mill, with a ball-to-material ratio of 2:1, a ball milling speed of 150-250 rpm / s, and a ball milling time of 3-6 h.

[0019] Specifically, in step (3), the laser powder bed fusion forming equipment includes a YLR-500 fiber laser, a laser forming chamber, an automatic powder spreading system, a protective atmosphere device, a computer control circuit system and a cooling circulation system; before forming, the sandblasted titanium alloy substrate is fixed on the workbench of the selective laser melting forming equipment and leveled, and then the forming cavity is sealed, evacuated and introduced into an inert gas protective atmosphere through a sealing device, thereby performing laser powder bed fusion forming to obtain the desired parts.

[0020] Preferably, in step (3), the laser power used by the laser powder bed fusion forming equipment is 375-475W, the laser scanning speed is 800-1400mm / s, the scanning interval is 60-100μm, the powder thickness is 30-50μm, and the island scanning strategy is adopted.

[0021] The present invention first discovered that during the laser forming process, TiH2 and XB6 powders react in situ in the molten pool to form Al 11 The series network structure with X3 as the main chain and Al3Ti as the nodes can act as a heterogeneous nucleation point to promote the transformation of coarse columnar crystals into fine equiaxed crystals in aluminum alloys, and can play a role in solid solution strengthening and grain refinement, thus achieving a significant improvement in laser formability and mechanical properties.

[0022] Beneficial effects:

[0023] (1) The present invention uses TiH2 and XB6 powder to reinforce aluminum-based composite materials, and can in situ generate an Al-based composite material under the action of high-energy laser. 11 The aluminum-based composite material is reinforced with a series network structure with X3 as the main chain and Al3Ti as the nodes. This structure can act as a heterogeneous nucleation point to promote the transformation of coarse columnar crystals of aluminum alloy to fine equiaxed crystals, and can play a synergistic role of solid solution strengthening and fine grain strengthening, which can achieve a significant improvement in laser formability and mechanical properties.

[0024] (2) The present invention can adjust the laser energy density by changing the laser power and the laser scanning speed. As the laser energy input of the powder bed changes, the thermodynamic and kinetic characteristics of the molten pool formed by the interaction between the laser and the powder bed also change. By reasonably selecting the laser process parameters and adjusting the laser energy input, the generation of metallurgical defects such as cracks and pores can be reduced, and a series network structure reinforced phase reinforced aluminum-based composite material with excellent formability and mechanical properties can be obtained.

[0025] (3) The present invention obtains a nanometer-sized series network structure reinforcement phase by introducing a micron-sized reinforcement phase, which can significantly reduce costs compared to directly adding nanoparticles, has good economic benefits and significantly improves mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0027] Figure 1 Schematic diagram of the series network structure reinforcement phase in laser-formed aluminum matrix composites.

[0028] Figure 2 Example 1: Optical microscope image of aluminum-based composite material formed by laser additive manufacturing.

[0029] Figure 3 Example 1 Microstructure image and EDS composition analysis of aluminum-based composite materials formed by laser additive manufacturing.

[0030] Figure 4 Example 1 Tensile property curve of aluminum-based composite material formed by laser additive manufacturing.

[0031] Figure 5 Optical microscope image of aluminum-based composite material formed by laser additive manufacturing in Comparative Example 1.

[0032] Figure 6 Comparative Example 1: Tensile properties curve of aluminum-based composite material formed by laser additive manufacturing.

[0033] Figure 7 Optical microscope image of aluminum-based composite material formed by laser additive manufacturing in Comparative Example 2.

[0034] Figure 8 Comparative Example 2: Tensile properties curve of aluminum-based composite material formed by laser additive manufacturing. DETAILED DESCRIPTION

[0035] The present invention can be better understood with reference to the following examples.

[0036] In the following embodiments, the aluminum-copper-lithium-nickel-zirconium alloy powder used has a particle size of 21-52 μm, wherein the copper content is 3.0-4.2 wt.%, the lithium content is 0.6-1.7 wt.%, the nickel content is 0.15-0.90 wt.%, the zirconium content is 0.1-0.8 wt.%, and the remainder is Al, and the purity is greater than 99.5%.

[0037] The particle size distribution range of the TiH2 metal powder used is 2-5 μm, and the purity is greater than 99.5%.

[0038] The particle size distribution range of the XB6 ceramic powder used is 2-5 μm, and the purity is greater than 99.5%.

[0039] Example 1

[0040] (1) Use a QM series planetary ball mill to evenly mix 98wt.% aluminum-copper-lithium-nickel-zirconium alloy powder, 1wt.% TiH2 metal powder, and 1wt.% LaB6 ceramic powder. The ball-to-material ratio is 2:1, argon is introduced into the ball mill as a protective gas, the ball milling speed is 200rpm / s, the ball milling time is 4.5h, and the ball milling mode is set to stop for 10min every 20min of operation to prevent over-temperature;

[0041] (2) Use Creo modeling software to draw models of 10 mm × 10 mm × 5 mm and 70 mm × 10 mm × 5 mm on a computer, and use Magics software to slice the three-dimensional model and set the laser processing parameters. The laser power is set to 425 W, the laser scanning speed is set to 1100 mm / s, the scanning pitch is 80 μm, the powder layer thickness is 40 μm, and the scanning strategy is an island scanning strategy. The data is then imported into the laser additive manufacturing equipment for subsequent laser forming.

[0042] (3) The aluminum-based composite powder obtained above is formed using an LPBF-150 laser powder bed melting device, which is equipped with a YLR-500 fiber laser with a wavelength of 1070 nm and a spot size of 70 μm. Before forming, the aluminum-based composite material is placed in the powder chamber, the aluminum substrate is fixed in the forming chamber, and argon gas is introduced into the device as a protective gas so that the oxygen content inside the device is less than 50 ppm. Subsequently, the desired parts are obtained through a layer-by-layer powder laying-melting-solidification process according to the above slicing data.

[0043] (4) The formed specimens were cut from the substrate, and blocks with a size of 10 mm × 10 mm × 5 mm were ground and polished according to the standard metallographic process for subsequent OM microstructure characterization.

[0044] Figure 1 The composite material includes an aluminum alloy matrix and Al2O3 uniformly dispersed in the aluminum alloy matrix. 11 X3 and Al3Ti series network structure reinforcement phase.

[0045] Wherein, the aluminum alloy matrix is ​​aluminum-copper-lithium-nickel-zirconium alloy; X is selected from any one of Ce, La, Nd, etc.; Al 11 X3 and Al3Ti series network structure reinforcement phase with Al 11 X3 is the main chain, Al3Ti is the node, and the series network structure reinforcement phase is evenly distributed in the aluminum alloy matrix.

[0046] like Figure 2 As shown in the figure, the laser formed aluminum matrix composite material sample has no cracks, only a small amount of pores, and the density reaches 99.8%, and all of them are fine equiaxed grains with an average grain size of ~3μm. Figure 3 As shown in the figure, through EDS composition analysis, it was found that Al 11 The block sample with the size of 70mm×10mm×5mm was cut into standard tensile pieces and then subjected to tensile test using CMT5205 universal testing machine. The tensile rate was set to 2mm / min. The obtained engineering stress-strain curve is shown in Figure 4 As shown in the figure, the tensile strength is 300MPa and the elongation is 5.5%, which is 34% higher than the strength of the laser-formed aluminum-copper-lithium-nickel-zirconium alloy sample (224.6MPa). This structure can serve as a heterogeneous nucleation point to promote the transformation of coarse columnar crystals of aluminum alloy to fine equiaxed crystals, and can play a synergistic role in solid solution strengthening and fine grain strengthening, which can achieve a significant improvement in laser formability and mechanical properties.

[0047] Example 2

[0048] (1) Use a QM series planetary ball mill to evenly mix 99wt.% aluminum-copper-lithium-nickel-zirconium alloy powder, 0.5wt.% TiH2 metal powder, and 0.5wt.% LaB6 ceramic powder. The ball-to-material ratio is 2:1, argon is introduced into the ball mill as a protective gas, the ball milling speed is 250rpm / s, the ball milling time is 3h, and the ball milling mode is set to stop for 10min every 20min to prevent the temperature from being too high;

[0049] (2) Use Creo modeling software to draw models of 10 mm × 10 mm × 5 mm and 70 mm × 10 mm × 5 mm on a computer, and use Magics software to slice the three-dimensional model and set the laser processing parameters. The laser power is set to 375 W, the laser scanning speed is set to 800 mm / s, the scanning spacing is 60 μm, the powder layer thickness is 30 μm, and the scanning strategy is an island scanning strategy. The data is then imported into the laser additive manufacturing equipment for subsequent laser forming.

[0050] (3) The aluminum-based composite powder obtained above is formed using an LPBF-150 laser powder bed melting device, which is equipped with a YLR-500 fiber laser with a wavelength of 1070 nm and a spot size of 70 μm. Before forming, the aluminum-based composite material is placed in the powder chamber, the aluminum substrate is fixed in the forming chamber, and argon gas is introduced into the device as a protective gas so that the oxygen content inside the device is less than 50 ppm. Subsequently, the desired parts are obtained through a layer-by-layer powder laying-melting-solidification process according to the above slicing data.

[0051] (4) The formed samples were cut from the substrate, and the blocks with the size of 10mm×10mm×5mm were ground and polished according to the standard metallographic process for subsequent OM microstructure characterization. The block samples with the size of 70mm×10mm×5mm were cut into standard tensile parts and then subjected to tensile tests using a CMT5205 universal testing machine with a tensile rate of 2mm / min. The final laser-formed sample had a density of 99.3% and a tensile strength of 293MPa, which was 30% higher than the laser-formed aluminum-copper-lithium-nickel-zirconium alloy sample (224.6MPa).

[0052] Example 3

[0053] (1) Use a QM series planetary ball mill to evenly mix 95wt.% aluminum-copper-lithium-nickel-zirconium alloy powder, 2.5wt.% TiH2 metal powder, and 2.5wt.% LaB6 ceramic powder. The ball-to-material ratio is 2:1, argon is introduced into the ball mill as a protective gas, the ball milling speed is 150rpm / s, the ball milling time is 6h, and the ball milling mode is set to stop for 10min every 20min of operation to prevent over-temperature;

[0054] (2) Use Creo modeling software to draw models of 10 mm × 10 mm × 5 mm and 70 mm × 10 mm × 5 mm on a computer, and use Magics software to slice the three-dimensional model and set the laser processing parameters. The laser power is set to 475 W, the laser scanning speed is set to 1400 mm / s, the scanning interval is 100 μm, the powder layer thickness is 50 μm, and the scanning strategy is an island scanning strategy. The data is then imported into the laser additive manufacturing equipment for subsequent laser forming.

[0055] (3) The aluminum-based composite powder obtained above is formed using an LPBF-150 laser powder bed melting device, which is equipped with a YLR-500 fiber laser with a wavelength of 1070 nm and a spot size of 70 μm. Before forming, the aluminum-based composite material is placed in the powder chamber, the aluminum substrate is fixed in the forming chamber, and argon gas is introduced into the device as a protective gas so that the oxygen content inside the device is less than 50 ppm. Subsequently, the desired parts are obtained through a layer-by-layer powder laying-melting-solidification process according to the above slicing data.

[0056] (4) The formed samples were cut from the substrate, and the blocks with the size of 10mm×10mm×5mm were ground and polished according to the standard metallographic process for subsequent OM microstructure characterization. The block samples with the size of 70mm×10mm×5mm were cut into standard tensile parts and then subjected to tensile tests using a CMT5205 universal testing machine with a tensile rate of 2mm / min. The final laser-formed sample had a density of 99.5% and a tensile strength of 286MPa, which was 27% higher than the strength of the laser-formed aluminum-copper-lithium-nickel-zirconium alloy (224.6MPa).

[0057] Comparative Example 1

[0058] This comparative example is carried out according to step 1 of the embodiment, except that in step (1), only 2 wt.% of TiH2 metal powder is used as the reinforcing phase to strengthen the aluminum-based composite material; its microstructure is as follows Figure 5 As shown in Figure 1, a large number of pores appeared in the aluminum-based composite material sample of Comparative Example 1. Since only TiH2 powder was added, only Al3Ti precipitation phase was formed in situ, and a series network structure reinforcement phase could not be formed. Under the action of high-energy laser, TiH2 metal powder melted to produce hydrogen, which increased the porosity and reduced the density of the sample to 92%. The obtained stress-strain curve is shown in Figure 1. Figure 6 As shown, the tensile strength is 234 MPa and the elongation is 1.8%, which are respectively reduced by 30% and 50% compared with Example 1, indicating that the reinforcing effect of TiH2 powder alone is limited.

[0059] Comparative Example 2

[0060] This comparative example is carried out according to step 1 of the embodiment, except that in step (1), only 2 wt.% of LaB6 metal powder is used as the reinforcing phase to strengthen the aluminum-based composite material; its microstructure is as follows Figure 7 As shown in the figure, a large number of cracks appeared in the aluminum-based composite material sample of Comparative Example 1. Since only LaB6 powder was added, only Al 11 La3 precipitates and fails to form a series network structure reinforcement phase. Due to the difference in thermal physical parameters between ceramic powder and aluminum alloy matrix, and the fine Al 11 The La3 precipitate phase as a heterogeneous nucleation site requires a large degree of supercooling for heterogeneous nucleation, so the grain refinement effect is weakened, the formation of thermal cracks cannot be suppressed, and the density of the sample is reduced to 95%; the obtained stress-strain curve is shown in Figure 8 As shown, the tensile strength is 201 MPa and the elongation is 0.78%, which are respectively reduced by 40% and 78% compared with Example 1. In particular, the elongation is significantly reduced and the material suffers from brittle fracture, indicating that the reinforcement effect of LaB6 powder alone is limited and leads to increased brittleness of the aluminum-based material.

[0061] The present invention provides a series of network structure reinforced phase reinforced aluminum matrix composite material and its preparation method and method, there are many methods and ways to implement the technical solution, the above is only the preferred embodiment of the present invention, it should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, these improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technology.

Claims

1. A series network structure reinforced phase reinforced aluminum matrix composite material, characterized in that: It includes an aluminum alloy matrix and Al 11 X3 and Al3Ti tandem network structure reinforcement phase; Wherein, the aluminum alloy matrix is ​​aluminum-copper-lithium-nickel-zirconium alloy; the X is selected from any one of Ce, La, and Nd; The Al 11 X3 and Al3Ti series network structure reinforcement phase with Al 11 X3 is the main chain, Al3Ti is the node, and the series network structure reinforcement phase is evenly distributed in the aluminum alloy matrix.

2. The method for preparing the aluminum-based composite material reinforced with a series network structure as claimed in claim 1, characterized in that: The following steps are involved: (1) uniformly mixing TiH2 metal powder, XB6 ceramic powder and aluminum alloy matrix powder to obtain composite powder; (2) Establish a 3D solid geometric model of the target part, slice the model and plan the laser scanning path, discretize the 3D solid into a series of 2D data, save and import them into the laser powder bed fusion forming equipment; (3) The laser powder bed fusion forming equipment rapidly melts and solidifies the composite powder in step (1) layer by layer according to the file imported in step (2); In step (1), the mass ratio of the TiH2 metal powder to the XB6 ceramic powder is 3:1-1:5; the total mass of the TiH2 metal powder and the XB6 ceramic powder accounts for 1-5 wt.% of the mass of the aluminum alloy matrix powder.

3. The method for preparing the aluminum-based composite material reinforced by a series network structure reinforcement phase according to claim 2, characterized in that: In step (1), the particle size of the TiH2 metal powder is in the range of 2-5 μm, and the purity is greater than 99.5%.

4. The method for preparing the aluminum-based composite material reinforced by a series network structure reinforcement phase according to claim 2, characterized in that: In step (1), the XB6 ceramic powder has a particle size range of 2-5 μm and a purity greater than 99.5%.

5. The method for preparing the aluminum-based composite material reinforced by a series network structure reinforcement phase according to claim 2, characterized in that: In step (1), the aluminum alloy matrix powder is an aluminum-copper-lithium-nickel-zirconium alloy, wherein the copper content is 3.0~4.2wt.%, the lithium content is 0.6~1.7 wt.%, the nickel content is 0.15~0.90 wt.%, the zirconium content is 0.1~0.8 wt.%, and the remainder is Al; the aluminum alloy powder has a particle size distribution range of 21~52 μm and a purity greater than 99.5%.

6. The method for preparing the aluminum-based composite material reinforced by a series network structure reinforcement phase according to claim 2, characterized in that: In step (1), TiH2 metal powder, XB6 ceramic powder and aluminum alloy matrix powder are uniformly mixed by ball milling in a planetary ball mill under the protection of inert gas.

7. The method for preparing the aluminum-based composite material reinforced by a series network structure reinforcement phase according to claim 6, characterized in that: The planetary ball mill adopts a QM series planetary ball mill, with a ball-to-material ratio of 2:1, a ball milling speed of 150-250 rpm / s, and a ball milling time of 3-6 h.

8. The method for preparing the aluminum-based composite material reinforced by a series network structure reinforcement phase according to claim 2, characterized in that: In step (3), the laser powder bed fusion forming equipment includes a YLR-500 fiber laser, a laser forming chamber, an automatic powder spreading system, a protective atmosphere device, a computer control circuit system and a cooling circulation system; before forming, the sandblasted titanium alloy substrate is fixed on the workbench of the selective laser melting forming equipment and leveled, and then the forming cavity is sealed, evacuated and introduced into an inert gas protective atmosphere through a sealing device, thereby performing laser powder bed fusion forming to obtain the desired parts.

9. The method for preparing the aluminum-based composite material reinforced by a series network structure reinforcement phase according to claim 2, characterized in that: In step (3), the laser power used by the laser powder bed fusion forming equipment is 375-475 W, the laser scanning speed is 800-1400 mm / s, the scanning interval is 60-100 μm, the powder thickness is 30-50 μm, and the island scanning strategy is adopted.

Citation Information

Patent Citations

  • Method for in situ producing aluminide reinforced layer on surface of aluminum alloy

    CN101532141A

  • Heat-resistant aluminum-based composite material and preparation method thereof

    CN113755727A